2020
DOI: 10.21203/rs.3.rs-36153/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Potential of Hematopoietic Stem Cells (Hsc) Against Sars-Cov-2 (Covid-19) With Virus Isolates From Indonesia (In Vitro Study)

Abstract: Background: The prevalence of COVID-19 cases in Indonesia until June 9th 2020, Government has confirmed the number of 32.076 positive cases from 34 provinces in Indonesia with 1.923 fatalities. Along with the development of technology, stem cell-based biological medical therapy, and stem cell-based immunotherapy were developed to find out its potential in the case of COVID-19 treatment besides using chemical drugs as a therapy.Methods: In this study, in vitro research will be conducted to determine the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A recent study demonstrated treatment for COVID-19 infection using HSCs. The study suggested that the mechanism of HSC to eliminate viruses is by reducing inflammatory cytokines and by increasing anti-inflammatory cytokines that make the virus inactive (Frias-Staheli et al, 2014;Purwati Sumorejo et al, 2020).…”
Section: Immunohistochemical Study Of Liver Tissuementioning
confidence: 99%
“…A recent study demonstrated treatment for COVID-19 infection using HSCs. The study suggested that the mechanism of HSC to eliminate viruses is by reducing inflammatory cytokines and by increasing anti-inflammatory cytokines that make the virus inactive (Frias-Staheli et al, 2014;Purwati Sumorejo et al, 2020).…”
Section: Immunohistochemical Study Of Liver Tissuementioning
confidence: 99%